Ijtihad Progresif dalam Penegakan Hukum Positif Islam di Pengadilan Agama tentang Pembagian Harta Bersama - Akhmad Khisni (Jurnal Hukum IUS QUIA IUSTUM, 2012)
The main problems discussed are: First, how the realization of the Islamic positive law reinforcement is in the Religious Court to create justice in the division of marital property in KHI (Islamic Law Compilation); second, what the form of of progressive ijtihad is in the Islamic positive law reinforcement in the Religious Court to create justice in the division of marital property in KHI (Islamic Law Compilation). This research uses normative juridical, descriptive in nature, through the data in form of Religious Court decisions using constructivism paradigm with qualitative analysis. The result of the research is as follows: First, in the division of marital property, the wife gets 2/3 (two-thirds) which is more than the husband who gets 1/3 (a third). This decision seems contradicting Article 97 KHI. Second, using the method ijtihad tatbiqi, ijtihad used in implementing the law by observing the facts and events as the background of the case, the judges find the appropriate clauses for the case after observing the relations between the background facts and event.